Economy-water nexus in agricultural sector: decomposing dynamics in water footprint by the LMDI - Su, Weihua; Chen, Sibo; Baležentis, Tomas; Chen, Ji (Technological and Economic Development of Economy, 2020)
Traditional economic activities induce environmental pressures. In order to ensure sustainable economic growth, one needs to decouple it from the environmental pressures. Sustainable growth of the agricultural sector is topical in the sense that economic activity supports rural populations, whereas the resulting environmental pressures may affect diverse groups of population. Thus, the analysis of water footprint related to crop farming is important in the sense of efficient resource use and sustainable development of agriculture in general. In this paper, we focus on Lithuanian crop farming and the related green and grey water footprints. Specifically, we decompose the changes in the water footprints during 2000–2016 by exploiting the Logarithmic Mean Divisia Index. Due to the expansion of the areas harvested, the scale effect appeared as an important driver of growth in green and grey water footprints. The shifts in spatial distribution of area harvested virtually had no influence on the dynamics in either of the water footprints. The crop-mix effect was much higher for the grey water footprint (51% over the period of 2000–2015) than it was the case for the green water footprint (21%). The yield growth induced growth in both green and grey water footprints.